Synthesized Attributes of Water Use by Regional Vegetation: A Key to Cognition of “Water Pump” Viewpoint - Xin-hui Huang; Fu-ke Yu; Xiao-ying Li; Yuan Zheng; Hua Yuan; Jian-gang Ma; Yan-xia Wang; Dan-hui Qi; Hong-bo Shao (The Scientific World Journal)
Recently, the frequent seasonal drought in Southwest China has brought considerable concerns and continuous heated arguments on the “water pump” viewpoint (i.e., the water demand from Hevea spp. and Eucalyptus spp. can be treated as a water pump) once again. However, such viewpoint just focused on water consumption from vegetation transpiration and its ecoenvironment impacts, which had not considered other attributes of vegetation, namely, water saving and drought resistance, and hydrological regulation (water conservation) into consideration. Thus, in this paper, the synthesized attributes of regional vegetation water use had been mainly discussed. The results showed that the study on such aspects as the characters of water consumption from vegetation transpiration, the potential of water saving and drought resistance, and the effects of hydrological regulation in Southwest China lagged far behind, let alone the report on synthesized attributes of water utilization with the organic combination of the three aspects above or the paralleled analysis. Accordingly, in this paper, the study on the synthesized attributes of water use by regional vegetation in Southwest China was suggested, and the objectives of such a special study were clarified, targeting the following aspects: (i) characters of water consumption from transpiration of regional typical artificial vegetation; (ii) potential of water saving and drought resistance of regional typical artificial vegetation; (iii) effects of hydrological regulation of regional typical artificial vegetation; (iv) synthesized attributes of water use by regional typical artificial vegetation. It is expected to provide a new idea for the scientific assessment on the regional vegetation ecoenvironment effects and theoretical guidance for the regional vegetation reconstruction and ecological restoration.